Pengaruh Suku Bunga, Perdagangan Internasional dan Nilai Tukar terhadap Pengangguran di ASEAN dalam Perspektif Islam - Rafi, M Al; Susanto, Is (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Unemployment is one of the key indicators in assessing a country's economic stability, including within the ASEAN region. Interest rates, international trade, and exchange rates are among the factors that influence the level of unemployment. In Islamic economics, unemployment is not only viewed as an economic problem but also as a form of social injustice that must be addressed through a sharia-based approach. This study aims to analyze the influence of interest rates, international trade, and exchange rates on the unemployment rate in five ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines, and Singapore) from the perspective of Islamic economics. This research employs a quantitative approach using panel data regression methods, processing secondary data from 2018 to 2024. The selection of the analytical model was carried out through the Chow and Hausman tests, which indicated that the Fixed Effect model was the most appropriate. The results of the study show that interest rates have a positive and significant effect on unemployment (0.0169 < 0.05), and exchange rates have a negative and significant effect on unemployment (0.0000 < 0.05), while international trade does not have a significant effect (0.1103 > 0.05). Simultaneously, the three variables have a significant effect on unemployment (0.000045 < 0.05). From an Islamic perspective, the solution to unemployment emphasizes fair wealth distribution, the prohibition of riba (usury), and the implementation of profit-sharing systems such as mudharabah and musyarakah.